Pengaruh Perputaran Modal kerja dan perputaran piutang terhadap tingkat Rentabilitas (studi kasus pada Koperasi Lamtamarga Karawang Periode 2017-2022) - Pasaribu, Erika; Sihabudin, Sihabudin; Fauji, Robby (Universitas Islam Kadiri, 2023)
The purpose of this study is to determine how working capital turnover and receivables turnover have an impact on the level of profitability in the Lamta Marga Karawang Cooperative from 2017 to 2022. This study used descriptive statistical verifiative quantitative techniques. This study utilizes the financial statements of the Latma Marga Karawang Cooperative from 2017 to 2022 as a population, with a sample time of 72 months (12 x 6). The results showed that the independent variable of working capital turnover had a partial effect on the level of profitability, with a sig of 0.000 < 0.05, and the independent variable of receivables turnover had no partial effect on the level of profitability, with a sig of 0.372 > 0.05. Simultaneously, the variables of working capital turnover and receivables turnover affect the profitability level of the Lamta Marga Karawang Cooperative for the 2017-2022 period, with a sig of 0.000 < 0.05, which means the variables of working capital turnover and receivables turnover contributed 64.7% in increasing profitability in the Lamtamarga Karawang Cooperative for the period 2017 - 2022, the remaining 35.3% was explained by other variables not explained in this study.